Inequality, redistribution and mobility - Rodríguez, Juan Gabriel; Bishop, John A. (Research on economic inequality, 2021)
Research on Economic Inequality is a well-established publication of quality research. This 28th volume features insightful and original papers from the 8th Society for the Study of Economic Inequality (ECINEQ) meeting. The first paper of this volume illustrates the trajectory of income inequality in wealthy countries over the course of recent decades, while the second carries out a comprehensive assessment of income redistribution through taxes and transfers across OECD countries over the last two decades. The next two papers cover the topic of income mobility, one interpreting the Bartholomew index of mobility in terms of a directional mobility index, and the second providing a framework for the measurement of income mobility over a range of time periods. A fifth paper studies the potential equalization of rising educational attainment. The next paper investigates the effect the number of children within different age groups has on poverty. In the seventh, it is shown that a social planner who seeks to efficiently reduce the aggregate relative deprivation of the population, coincides with the Rawlsian social planner. Finally, the last paper generalizes the Oaxaca-Blinder approach to measure wage discrimination under imperfect information